Macromol. Rapid Commun. 19/2013. Issue 19 (2nd October 2013) - Huang, Jin; Zhang, Qiang; Li, Guang‐Zhao; Haddleton, David M.; Wallis, Russell; Mitchell, Daniel; Heise, Andreas; Becer, C. Remzi
<x xml:space="preserve">Abstract</x> Front Cover: Synthetic glycopolymers and their interactions with lectins have attracted great attention not only in synthetic polymer chemistry but also in chemical biology. Natural glycans exhibit a GlycoCode that runs many biological processes in our body. Creating synthetic mimics of these compounds and understanding the GlycoCode is crucial in immunology, biomaterials, and drug delivery applications. Herein, the binding properties of glycopolypeptides and dendritic cell lectin, DC‐SIGN, are investigated using surface plasmon resonance. These structures are found to effectively inhibit the binding between HIV glycoprotein, gp120, and DC‐SIGN. Further details can be found in the article by Huang, Q. Zhang, G.‐Z. Li, D. M. Haddleton, R. Wallis, D. Mitchell, A. Heise, * and C. R. Becer* on page 1542. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>